Estudio de factibilidad para la creación de una sucursal de la farmacia comunitaria Alexandra en el barrio Orellana de la ciudad de Nueva Loja, provincia de Sucumbíos - Umaquiza Biscarra, Karina Margarita (2016)
he present study was developed with the aim to "determine the feasibility of setting up a branch of the Alexandra community pharmacy in Orellana neighborhood in the city of Nueva Loja, Sucumbios province, to do research methods and techniques were used, including inductive, deductive, analytical and synthetic, and the interview and survey; market research was carried out thanks to information obtained from the sample taken from families living in Nueva Loja, corresponding to 394, while the analysis of supply concentrated in 28 pharmacies in the town. The results of the market research show that there is an unmet demand for antiviral 108,795; 49 697 94152 antibiotics and anti-inflammatory for the first year of life of the project; Also in the technical study of 37,234 installed customers during capacity it is established; starting with a capacity utilization of 75% because it is a new business, considering the average purchase amount of drugs per person capacity used of 66,556 medicines sold in the year was established, it was also established that the optimal location of the project is in Barrio Orellana, streets and Sauces Las Balsas and the average time of attention to each customer is 14 min. In organizational study it found that the pharmacy requires 5 people to attend efficiently to customers. In the financial study an investment of $74,966.89 was established; money that will be financed by 44% 6 contribution of partners and through the remaining credit in the Bank Pichincha 56%. The average unit cost per drug is $ 6.27 antiviral drugs, $ 8.76 antibiotics, anti-inflammatory and $ 9.40; from costing the sale price was established, considering the average profit margin by type of drugs established under the implanted analysis conducted by the Technical Secretariat of the National Council of fixing and Medicines Prices Review prices, based on which the 21% profit margin on antiviral drugs, antibiotics 22%, and 20% in inflammatory determined. Finally, net income for the first year of life of $ 67,242.78 and $ 114,068.05 fifth year was calculated; and the estimated cash flow is $ 70.618,29 the first year and $ 128,555.92 for the fifth year. The financial evaluation yielded the following results: The VAN found for the project is $ 230,431.76; IRR is 103.79% higher than the rate of cost of capital is 15%; the cost-benefit ratio showed that for every dollar invested pharmacy earn $ 0.22; investment is expected to recover in one year, 11 months and 11 days shorter than the useful life of the project, while the sensitivity analysis it was determined that the project supports increased costs of up to 14.85% and a decrease in their incomes up to 12.19%. Because the results are recommended investment, since according to the analyzes carried out the project is profitable and will create new jobs both direct and indirect, contributing to the revitalization of the economy of this part of the country.